Predictors of improvement of UI-related quality of life after a 3-month PFMT program - Pedro Miguel Gonçalves Cardoso Teixeira (2022)
Abstract Introduction and Hypothesis Urinary incontinence (UI) is one of the main causes of reduction in quality of life (QoL) in women. Pelvic floor muscle training (PFMT) is a first-line conservative management for UI. This study aimed to determine the predictors of UI-related quality of life improvement in female patients with stress UI (SUI) and mixed UI (MUI), after PFMT. Methods Clinical data of women participating in a previous prospective randomized controlled trial that tested the effectiveness of an hybrid telerehabilitation program in relation to a traditional face-to-face model among female patients with SUI and MUI was obtained. This dataset was used to evaluate the potential predictors of QoL improvement after the program. The primary outcome was defined as the improvement in UI-related QoL measured by the King's Health Questionnaire (KHQ) global score, and was assessed at baseline and 3 months after the intervention. Results A total of 34 women aged 45.5 (± 7.2) years were included after an univariate analysis. The following variables were considered predictors of the primary outcome when assessed in multiple linear regression models, adjusted for the baseline KHQ global score: daily losses with sneezing or coughing (β=-7.7, 95% Confidence Interval (CI): -13.6 to -1.9; p=0.012), urgency (β=-5.8, 95% CI: -10.7 to -0.9; p=0.023), and constipation (β=6.89, 95% CI: 1.5 to 12.3; p=0.014). Conclusion Losses with sneezing or coughing, urgency, and absence of constipation were found to be predictors of UI-related QoL improvement after a 3-month PFMT program.